2017
DOI: 10.1038/nn.4490
|View full text |Cite|
|
Sign up to set email alerts
|

Overlearning hyperstabilizes a skill by rapidly making neurochemical processing inhibitory-dominant

Abstract: Overlearning refers to the continued training of a skill after performance improvement has plateaued. Whether overlearning is beneficial is a question in our daily lives that has never been clearly answered. Here, we report a new important role: Overlearning abruptly changes neurochemical processing to hyper-stabilize and protect trained perceptual learning from subsequent new learning. Usually, learning immediately after training is so unstable that it can be disrupted by subsequent new learning, unless waiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
259
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(274 citation statements)
references
References 65 publications
13
259
2
Order By: Relevance
“…Healthy brain function relies on GABAergic inhibitory processes, and understanding GABAergic mechanisms in both healthy and pathological brain function has been one core focus of neuroscience. MRS measurements of GABA have been associated with individual differences in hemodynamic and electrophysiological signals (Donahue et al, 2010; Hu et al, 2013; Kapogiannis et al, 2013; Muthukumaraswamy et al, 2009) and a number of measures of cognition (Fujihara et al, 2015; Shibata et al, 2017; Yoon et al, 2016) and behavior (Boy et al, 2011; Greenhouse et al, 2017; Puts et al, 2011; Silveri et al, 2013). Differential levels of GABA have been observed in a number of neuropsychiatric disorders, such as schizophrenia (Kegeles et al, 2012; Öngür et al, 2010; Rowland et al, 2016; Yoon et al, 2010) and depression (Bhagwagar et al, 2008; Hasler et al, 2007; Price et al, 2009), neurodevelopmental disorders such as autism spectrum disorder (Drenthen et al, 2016; Gaetz et al, 2014; Puts et al, 2016) and attention deficit hyperactivity disorder (Bollmann et al, 2015; Edden et al, 2012a), and neurological diseases, such as Parkinson’s disease (Emir et al, 2012), amyotrophic lateral sclerosis (Foerster et al, 2012; Foerster et al, 2013) and diabetic neuropathy (Petrou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy brain function relies on GABAergic inhibitory processes, and understanding GABAergic mechanisms in both healthy and pathological brain function has been one core focus of neuroscience. MRS measurements of GABA have been associated with individual differences in hemodynamic and electrophysiological signals (Donahue et al, 2010; Hu et al, 2013; Kapogiannis et al, 2013; Muthukumaraswamy et al, 2009) and a number of measures of cognition (Fujihara et al, 2015; Shibata et al, 2017; Yoon et al, 2016) and behavior (Boy et al, 2011; Greenhouse et al, 2017; Puts et al, 2011; Silveri et al, 2013). Differential levels of GABA have been observed in a number of neuropsychiatric disorders, such as schizophrenia (Kegeles et al, 2012; Öngür et al, 2010; Rowland et al, 2016; Yoon et al, 2010) and depression (Bhagwagar et al, 2008; Hasler et al, 2007; Price et al, 2009), neurodevelopmental disorders such as autism spectrum disorder (Drenthen et al, 2016; Gaetz et al, 2014; Puts et al, 2016) and attention deficit hyperactivity disorder (Bollmann et al, 2015; Edden et al, 2012a), and neurological diseases, such as Parkinson’s disease (Emir et al, 2012), amyotrophic lateral sclerosis (Foerster et al, 2012; Foerster et al, 2013) and diabetic neuropathy (Petrou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Training two related skills in close succession is known to result in interference (Cantarero et al 2013;Leow et al 2013;Wigmore, Tong, and Flanagan 2002;Sing and Smith 2010;Brashers-Krug, Shadmehr, and Bizzi 1996;Shadmehr and Brashers-Krug 1997;Seitz et al 2005;Yotsumoto, Chang, et al 2009;Shibata et al 2017). It is thought that such interference is due to competition in LTP processes associated with each task (Cantarero et al 2013;Ziemann et al 2004;Stefan et al 2006) but direct evidence for this mechanism has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of interference have been observed: anterograde interference (i.e., new learning disrupting future learning) and retrograde interference (i.e., new learning disrupting a previous learning). Both types of interference are commonly observed across motor, perceptual, and cognitive learning (Cantarero et al 2013;Leow et al 2013;Wigmore, Tong, and Flanagan 2002;Sing and Smith 2010;Brashers-Krug, Shadmehr, and Bizzi 1996;Shadmehr and Brashers-Krug 1997;Seitz et al 2005;Yotsumoto, Chang, et al 2009;Shibata et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, perceptual learning studies in the visual domain support this notion. One such study by Shibata et al (2017) found that participants who achieved more stability in their learning of a visual skill by overlearning (continuing to train on a skill after mastery) were not only protected against interference from a second task, but they also retained learning of the first task when assessed the following day as compared to a group that received the typical amount of training. A similar study found that participants who trained on a perceptual task until performance reached asymptote improved after a period of sleep, but those who stopped training prior to that point did not, which suggests a role for stability in sleep-mediated consolidation of newly learned skills (Hauptmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%